2020
DOI: 10.1088/1674-4527/20/10/161
|View full text |Cite
|
Sign up to set email alerts
|

Binary Population Synthesis

Abstract: Binary interactions lead to the formation of intriguing objects, such as compact binaries, supernovae, gamma ray bursts, X-ray binaries, pulsars, novae, cataclysmic variables, hot subdwarf stars, barium stars and blue stragglers. To study the evolution of binary populations and the consequent formation of these objects, many methods have been developed over the years, for which a robust approach named binary population synthesis (BPS) warrants special attention. This approach has seen widespread application in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 124 publications
0
52
0
Order By: Relevance
“…This is consistent with findings by other studies on isolated binary evolution populations (e.g., Chruślińska et al 2018;Santoliquido et al 2021), which indicated that matching the observed NSNS rate might require higher values for 𝛼 CE and/or smaller SN natal kicks. The NSNS rates could also relatively increase by changes in the mass transfer stability prescriptions (𝜁) and envelope binding energy models (𝜆), which are not explored in our study (see Han et al 2020;Lau et al 2021, and references therein). Future observations and simulations can further constrain this.…”
Section: Comparison With Gw Mergersmentioning
confidence: 86%
“…This is consistent with findings by other studies on isolated binary evolution populations (e.g., Chruślińska et al 2018;Santoliquido et al 2021), which indicated that matching the observed NSNS rate might require higher values for 𝛼 CE and/or smaller SN natal kicks. The NSNS rates could also relatively increase by changes in the mass transfer stability prescriptions (𝜁) and envelope binding energy models (𝜆), which are not explored in our study (see Han et al 2020;Lau et al 2021, and references therein). Future observations and simulations can further constrain this.…”
Section: Comparison With Gw Mergersmentioning
confidence: 86%
“…Here we describe the terms in this equation, which allows us to highlight the broad range of physics involved and to comment on the key uncertainties. In practice, most modern models rely on some form of population synthesis, where large numbers of stellar binaries are evolved in order to compute the yield, frequently by using simplified recipes to reduce computational cost (Postnov and Yungelson 2014;Han et al 2020).…”
Section: Isolated Binary Evolution With Mass Transfermentioning
confidence: 99%
“…The binary fraction of OB stars increases as the spectral type goes to early (Guo et al 2021), and O stars in cluster, associations, and runaways have binary fraction (70%) higher than those in field environment (40%; Chini et al 2012). These observational studies challenge the accepted predominance of the single star evolutionary channel and complicate the exact determination of the evolutionary status and final fates of these stars (Han et al 2020).…”
Section: Introductionmentioning
confidence: 99%